2015
DOI: 10.3390/ijms16047551
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic Evaluation of MgO Nanoparticles and Their Effect on the Expression of ROS Genes

Abstract: Water-dispersible MgO nanoparticles were tested to investigate their cytotoxic effects on oxidative stress gene expression. In this in vitro study, genes related to reactive oxygen species (ROS), glutathione S-transferase (GST) and catalase, were quantified using real-time polymerase chain reactions (molecular level) and molecular beacon technologies (cellular level). The monodispersed MgO nanoparticles, 20 nm in size, were used to treat human cancer cell lines (liver cancer epithelial cells) at different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 34 publications
0
20
2
Order By: Relevance
“…We suspect that MgO is not too toxic for applications as a candidate for disease or cancer diagnosis, especially in the biomedical fields. In many other studies, results indicated that MgO nanomaterials are less toxic due to their smooth morphology, which reflects that the toxicity of nanomaterials is morphology and size/concentration dependent 3 , 39 . Cell viability is dependent on MgO concentration in experiments conducted in darkness and with 660 nm laser light.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…We suspect that MgO is not too toxic for applications as a candidate for disease or cancer diagnosis, especially in the biomedical fields. In many other studies, results indicated that MgO nanomaterials are less toxic due to their smooth morphology, which reflects that the toxicity of nanomaterials is morphology and size/concentration dependent 3 , 39 . Cell viability is dependent on MgO concentration in experiments conducted in darkness and with 660 nm laser light.…”
Section: Resultsmentioning
confidence: 83%
“…Kumaran investigated MgO nanoparticles (NP) with 20 nm size via the GST and ROS gene mechanism. The results showed that 150 µg/mL MgO nanoparticle dispersions liberate significant cytotoxins 3 . MgO NPs proved to be a promising material for biomedical applications due in cancer therapy, nano-cryosurgery, and hyperthermia.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different apoptotic pathways, the intrinsic mitochondrial apoptotic pathway plays a major role in metal oxide nanoparticle-induced cell death, since mitochondria are 1 of the major target organelles for nanoparticle-induced oxidative stress. [34][35][36][37][38] Ghobadian et al 26 reported MgO nanoparticles induced cellular apoptosis and intracellular ROS in zebrafish embryos. However, in the present study, MgO nanoparticles caused cell death through the other pathways than apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, MgO NPs were found to be least effective in inducing cell death in human astrocytoma U87 cells . Another study conducted on human liver epithelial cancer cell line for genotoxic effects of MgO NPs, did not produce significant effects compared with control experiments at the investigated concentrations . A few in vivo investigations with MgO NPs are available.…”
Section: Introductionmentioning
confidence: 95%